2007
DOI: 10.1073/pnas.0704342104
|View full text |Cite
|
Sign up to set email alerts
|

Genomics, biogeography, and the diversification of placental mammals

Abstract: Previous molecular analyses of mammalian evolutionary relationships involving a wide range of placental mammalian taxa have been restricted in size from one to two dozen gene loci and have not decisively resolved the basal branching order within Placentalia. Here, on extracting from thousands of gene loci both their coding nucleotide sequences and translated amino acid sequences, we attempt to resolve key uncertainties about the ancient branching pattern of crown placental mammals. Focusing on Ϸ1,700 conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
130
2
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 50 publications
12
130
2
3
Order By: Relevance
“…Subsequent rounds of duplication then produced a total of four HBB-like gene copies that have each retained an unconverted HBD-like downstream flanking sequence. (21,22,49,50). Diagonal slashes indicate gaps in genomic coverage.…”
Section: Genomic Structure and Orthologous Relationships In Atlantogementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent rounds of duplication then produced a total of four HBB-like gene copies that have each retained an unconverted HBD-like downstream flanking sequence. (21,22,49,50). Diagonal slashes indicate gaps in genomic coverage.…”
Section: Genomic Structure and Orthologous Relationships In Atlantogementioning
confidence: 99%
“…Eutherian mammals are classified into four superordinal groups: Afrotheria (which includes elephants, hyraxes, manatees, aardvarks, tenrecs, and allies), Xenarthra (which includes sloths, armadillos, and anteaters), Laurasiatheria (which includes bats, eulipotyphlans, pangolins, carnivores, perrisodactyls, and cetartiodactyls), and Euarchontoglires (which includes primates, tree shrews, colugos, rabbits, and rodents). Recent phylogenomic studies have demonstrated that a clade (Atlantogenata) composed of Afrotheria and Xenarthra is the sister group of all remaining members of the eutherian crown group (Boreoeutheria) (21,22). The inferred structure of the ␤-globin gene cluster in the common ancestor of Boreoeutheria is: 5Ј--␥--␦-␤-3Ј (13,14,16,23).…”
mentioning
confidence: 99%
“…Based on the fact that placental mammal groups of Afrotheria, Xenarthra, and Boreotheria originated in Africa, South America, and Laurasia, respectively, the divergence of these mammals has been proposed to be linked to the separation of continents and subsequent land mass drift (3,(15)(16)(17). Paleogeological estimates reported by Smith et al (18) indicate that Laurasia (where Boreotheria originated) separated first from Pangaea at 148-138 Ma and that the supercontinent Gondwana in the Southern Hemisphere divided into Africa and South America at 105 Ma.…”
mentioning
confidence: 99%
“…(B) Geographic transitions at the time of separation of the three lineages during the Cretaceous. (Left terrestrial globe) Possible overlapping geographical distribution of the three placental lineages before continental drift, the expected period of genetic flow between the lineages; (right terrestrial globe) separation of the continents and divergence of placental lineages possibly prohibiting further gene flow (Murphy et al 2001b;Wildman et al 2007). Roman numerals indicate exchanges of genetic material between the species shown in A.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies of large-scale sequences (e.g., Hallström et al 2007) and previous studies of smaller data sets could not significantly confirm an Afrotherian root (e.g., Madsen et al 2001;Waddell et al 2001;Delsuc et al 2002;Amrine-Madsen et al 2003). A sistergroup relationship of Afrotheria and Xenarthra (Atlantogenata) also received significant support in analyses of sequences from ;1700 conserved genome loci (Wildman et al 2007), 2840 protein-coding genes (Hallström et al 2007), and mitochondrial genomes (Kjer and Honeycutt 2007); and this was recently confirmed by large-scale analyses of 2.8 Mbp of protein-coding data (Hallström and Janke 2008) and large-scale genomic sequences (Prasad et al 2008). Thus, despite many different molecular studies, the basal origin of placental mammals remains controversial and unresolved.…”
mentioning
confidence: 92%